Ancient DNA from the Schild site in Illinois: Implications for the Mississippian transition in the Lower Illinois River Valley. Issue 3 (24th November 2014) - Reynolds, Austin W.; Raff, Jennifer A.; Bolnick, Deborah A.; Cook, Della C.; Kaestle, Frederika A.
ABSTRACT Archaeologists have long debated whether rapid cultural change in the archaeological record is due to in situ developments, migration of a new group into the region, or the spread of new cultural practices into an area through existing social networks, with the local peoples adopting and adapting practices from elsewhere as they see fit (acculturation). Researchers have suggested each of these explanations for the major cultural transition that occurred at the beginning of the Mississippian period (AD 1050) across eastern North America. In this study, we used ancient DNA to test competing hypotheses of migration and acculturation for the culture change that occurred between the Late Woodland (AD 400–1050) and Mississippian (AD 1050–1500) periods in the Lower Illinois River Valley. We obtained sequences of the first hypervariable segment of the mitochondrial genome (mtDNA) from 39 individuals (17 Late Woodland, 22 Mississippian) interred in the Schild cemetery in western Illinois, and compared these lineages to ancient mtDNA lineages present at other sites in the region. Computer simulations were used to test a null hypothesis of population continuity from Late Woodland to Mississippian times at the Schild site and to investigate the possibility of gene flow from elsewhere in the region. Our results suggest that the Late Woodland to Mississippian cultural transition at Schild was not due to an influx of people from elsewhere. Instead, it is more likely that the transition to Mississippian cultural practices at this site was due to a process of acculturation. Am J Phys Anthropol 156:434–448, 2015. © 2014 Wiley Periodicals, Inc.